My Choice: Female Contraceptive Use Autonomy in Bangladesh - Niels-Hugo Blunch (Global Labor Organization (GLO), 2018)
Previous research has examined the incidence and correlates of contraceptive use and of several dimensions of female autonomy but only rarely the intersection of the two: female contraceptive use autonomy (CUA). Using a nationally representative household survey for two cohorts of married women, I examine female CUA incidence and correlates in Bangladesh focusing on the role of education. Female CUA is found to differ substantially across cohorts, with women from the younger cohort being far more likely to have complete autonomy over contraceptive use than women from the older cohort. Detailed decompositions reveal that the improvement in education across cohorts is the main correlate of the improved generational CUA gap. Health knowledge, especially knowledge that the use of condoms can help avoid contracting HIV/AIDS, is found to be part of the transmission mechanism between female education and female CUA but also to additionally exert its own, additional influence on CUA. I also discuss the implications of the analysis conducted here for the specification of spousal education variables and geographic fixed effects for future related research.
Keywords: D13; I12; I21; 330; Contraceptive use; female autonomy; spousal education differentials; gender norms; decomposition analysis; Bangladesh